2016
DOI: 10.1103/physreva.93.042313
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian continuous-time quantum walks on lattices with dynamical noise

Abstract: We address the dynamics of continuous-time quantum walks on one-dimensional disordered lattices inducing dynamical noise in the system. Noise is described as time-dependent fluctuations of the tunneling amplitudes between adjacent sites, and attention is focused on non-Gaussian telegraph noise, going beyond the usual assumption of fast Gaussian noise. We observe the emergence of two different dynamical behaviors for the walker, corresponding to two opposite noise regimes: slow noise (i.e. strong coupling with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 84 publications
1
64
0
Order By: Relevance
“…, and we find the Lindblad-Kossakowski master equation3. In general, the memory kernel can lead to non-Markovian dynamics depending on the structure and time scale of the Hamiltonian, as for example demonstrated for random telegraph noise (RTN) and 1/ f -noise78. Indeed, also a Markovian stochastic process Ω( t ) (as in the case of RTN, where the time correlation is ) can lead to non-Markovian dynamics of the quantum system it is coupled to.…”
Section: Modelmentioning
confidence: 69%
See 1 more Smart Citation
“…, and we find the Lindblad-Kossakowski master equation3. In general, the memory kernel can lead to non-Markovian dynamics depending on the structure and time scale of the Hamiltonian, as for example demonstrated for random telegraph noise (RTN) and 1/ f -noise78. Indeed, also a Markovian stochastic process Ω( t ) (as in the case of RTN, where the time correlation is ) can lead to non-Markovian dynamics of the quantum system it is coupled to.…”
Section: Modelmentioning
confidence: 69%
“…Therefore, in the last few years several theoretical proposals for the characterization of the environment according to whether it can generate Markovian or non-Markovian dynamics of the system to which it is coupled have been put forward, and a full hierarchy of non-Markovianity6 has been introduced. In particular, it has been shown that classical environments exhibiting time-correlated random fluctuations can lead to non-Markovian quantum dynamics78. The structure of such an environment can be probed by coupling a (typically small, e.g.…”
mentioning
confidence: 99%
“…Also the effects of static noise (resulting in lattice disorder) could be explored in the case of identical particles-due to their role in phenomena like Anderson localization or the transition from quantum to classical random walks [119][120][121][122]-in order to explore differences, if present, with the distinguishable particle case [66].…”
Section: Discussionmentioning
confidence: 99%
“…Uchiyama et al [17] have analyzed the effect of spatial and temporal correlations on EET in a multi-site model by using a Ornstein-Uhlenbeck noise process to describe the environment, and observe that negative spatial correlation of the noise is the most effective in helping the EET. The effect of RTN on transport via continuous-time quantum walks has been studied on lattices [30,31], also in presence of spatial correlations [32]. Its effect on the non-Markovianity of the dynamics of the spin-boson model has also been considered [33].…”
Section: Introductionmentioning
confidence: 99%